Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Effect of single dose N-acetylcysteine administration on resting state functional connectivity in schizophrenia - Grant McQueen; Aderlee Lay; John Lally; Anthony S. Gabay; Tracy Collier; David J. Lythgoe; Gareth J. Barker; James M. Stone; Philip McGuire; James H. MacCabe; Alice Egerton (Psychopharmacology, 2020)
Rationale There is interest in employing N-acetylcysteine (NAC) in the treatment of schizophrenia, but investigations of the functional signatures of its pharmacological action are scarce. Objectives The aim of this study was to identify the changes in resting-state functional connectivity (rs-FC) that occur following administration of a single dose of NAC in patients with schizophrenia. A secondary aim was to examine whether differences in rs-FC between conditions were mediated by glutamate metabolites in the anterior cingulate cortex (ACC). Methods In a double-blind, placebo-controlled crossover design, 20 patients with schizophrenia had two MRI scans administered 7 days apart, following oral administration of either 2400 mg NAC or placebo. Resting state functional fMRI (rsfMRI) assessed the effect of NAC on rs-FC within the default mode network (DMN) and the salience network (SN). Proton magnetic resonance spectroscopy was used to measure Glx/Cr (glutamate plus glutamine, in ratio to creatine) levels in the ACC during the same scanning sessions. Results Compared to the placebo condition, the NAC condition was associated with reduced within the DMN and SN, specifically between the medial pre-frontal cortex to mid frontal gyrus, and ACC to frontal pole (all p < 0.04). There were no significant correlations between ACC Glx/Cr and rs-FC in either condition ( p > 0.6). Conclusions These findings provide preliminary evidence that NAC can reduce medial frontal rs-FC in schizophrenia. Future studies assessing the effects of NAC on rs-FC in early psychosis and on repeated administration in relation to efficacy would be of interest.

Effects of N-acetylcysteine on brain glutamate levels and resting perfusion in schizophrenia - Grant McQueen; John Lally; Tracy Collier; Fernando Zelaya; David J. Lythgoe; Gareth J. Barker; James M. Stone; Philip McGuire; James H. MacCabe; Alice Egerton (Psychopharmacology, 2018)

Seasonal Variation of Total Dissolved Arsenic and Arsenic Speciation in A Polluted Surface Waterway - Andrew G. Gault; David A. Polya; Paul R. Lythgoe (Environmental Geochemistry and Health, 2003)